Chinese Women’s Participation in Emerging New Olympic Sports - Bai, Huiqi (Πανεπιστήμιο Πελοποννήσου, 2024)
The purpose of the current study is to explore the impact of elite sports in emerging new Olympic sports on female participation intentions in mass sports. Taking female's self-perception of elite sports as an entry point, this study aims to analyse the effects of female elite events perceived value, behavioural attitudes, and sport publicity on female's continuous participation in mass sports in the emerging new Olympic sports. By building a Structural Equation Model and proposing hypotheses, esports, an emerging new Olympic sport, has been selected to conduct a questionnaire survey on 512 Chinese female participation in esports by combining offline and online methods. The results were statistically analysed to validate the relationship between the variables. The results indicated that in emerging new Olympic sports, elite events perceived value positively which affected female continuous participation intention, behavioural attitude partially mediated the effect of elite events perceived value on female continuous participation intention, and sport publicity partially mediates the effect of elite events perceived value on behavioural attitude. Furthermore, the development of Olympic sports in China requires further efforts to enhance the popularity of female sports in terms of the quality of the value of elite events.
Keywords: Ηλεκτρονικός αθλητισμός; Ολυμπιακοί αγώνες - Κίνα; Ολυμπιακά αθλήματα - Γυναίκες - Κίνα; Αθλητισμός για γυναίκες - Κίνα; Esports; Olympics - China; Olympic games - Women - China; Sports for women - China; emerging new Olympic sports; Esports; Chinese female; participation intentions